1980
DOI: 10.1007/bf00489769
|View full text |Cite
|
Sign up to set email alerts
|

The histochemical characterization of the coupling state of skeletal muscle mitochondria

Abstract: Isolated mitochondria from skeletal muscles of human and animals with neuromuscular diseases may reveal a loosely coupled state of oxidative phosphorylation, which is characterized by a normal phosphorylation in the presence of a phosphate acceptor and a maximal respiration in the absence of a phosphate acceptor. Moreover in these cases activity of mitochondrial Mg2+-stimulated ATPase is strongly increased and cannot be stimulated by the uncoupler 2,4-dinitrophenol. In this communication a histochemical techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 57 publications
1
18
0
Order By: Relevance
“…Morphologic examination, including enzyme histochemical and ultrastructural analysis of muscle tissue, was performed as described (10). Enzyme histochemical staining for mitochondrial Mg2+ ATPase was performed as described (27). Biochemical investigation of the respiratory chain function was done on isolated intact muscle mitochondria with polarographic measurements as described (10,28) and in disrupted isolated mitochondria by spectrophotometric methods as described (1 0).…”
Section: Methodsmentioning
confidence: 99%
“…Morphologic examination, including enzyme histochemical and ultrastructural analysis of muscle tissue, was performed as described (10). Enzyme histochemical staining for mitochondrial Mg2+ ATPase was performed as described (27). Biochemical investigation of the respiratory chain function was done on isolated intact muscle mitochondria with polarographic measurements as described (10,28) and in disrupted isolated mitochondria by spectrophotometric methods as described (1 0).…”
Section: Methodsmentioning
confidence: 99%
“…The method is a modification of that published by Rosenblatt et al (1987), which is in tum a combination of two previously reported techniques (Meijer and Vloedman, 1980;Meijer, 1970). The histochemical bases of the staining reaction are those reported by Meijer (1970) and Meijer and Vossenberg (1977) and quoted by Rosenblatt et al (1987).…”
Section: Discussionmentioning
confidence: 99%
“…This staining is weak in basal conditions but increases under the action of dinitrophenot (uncoupler) Meijer and Vloedman 1980).…”
Section: Histoenzymologymentioning
confidence: 99%